2018
DOI: 10.1002/fsn3.682
|View full text |Cite
|
Sign up to set email alerts
|

Antiwrinkle and antimelanogenesis activity of the ethanol extracts of Lespedeza cuneata G. Don for development of the cosmeceutical ingredients

Abstract: To develop the ingredient with the cosmeceutical function, the antiwrinkle and antimelanogenesis effects of the ethanol extract of Lespedeza cuneata G. Don were investigated. DPPH radical scavenging activity was significantly increased with the extract of L. cuneata G. Don. Cell viability on CCD986Sk human fibroblast was also increased by the ethanol extract of L. cuneata G. Don. The inhibitory function of the extract of L. cuneata G. Don on collagenase, elastase, and tyrosinase was evaluated. Protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In addition, extracts of L. cuneata were reported to have hepatoprotective and antidiabetic effects [4], anticancer and antioxidative activity, and inhibitory effects on cell proliferation [5]. The useful cosmetic effects of L. cuneata extracts, such as antiwrinkle, antimelanogenic, anti-aging, and anti-oxidative effects, have also been reported [6,7]. L. cuneata also showed pharmacological effects against male and female diseases, such as protective effects against testicular and ovarian diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, extracts of L. cuneata were reported to have hepatoprotective and antidiabetic effects [4], anticancer and antioxidative activity, and inhibitory effects on cell proliferation [5]. The useful cosmetic effects of L. cuneata extracts, such as antiwrinkle, antimelanogenic, anti-aging, and anti-oxidative effects, have also been reported [6,7]. L. cuneata also showed pharmacological effects against male and female diseases, such as protective effects against testicular and ovarian diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found in a screening test that the MeOH extract of L. cuneata exerted inhibitory effect on metabolic activity in MCF-7 human breast cancer cells, which led us to perform further phytochemical analysis and identify the bioactive compound(s) responsible for these effects. Bioassay-guided fractionation and chemical investigation of the MeOH extract led to the isolation of nine compounds (four lignan glycosides (1)(2)(3)(4), three flavonoid glycosides (5)(6)(7), and two phenolic compounds (8 and 9)). The structures of the isolated compounds were identified by LC-MS analysis and their spectroscopic data and physical data were compared with previously reported values.…”
Section: Introductionmentioning
confidence: 99%
“…Over-produced melanin should be controlled to maintain the skin integrity. That is why the discovery of novel tyrosinase inhibitors for the development of cosmeceutical formulations has received a significant interest [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies on bioactive materials isolated from plants that are currently used in cosmeceutical formulations, but very few studies on bioactive materials from bacteria are available [9,21,[24][25][26][27]31]. This study aimed to evaluate the cosmeceutical potential of ethyl acetate extracts from the bacterial strain Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…New tyrosinase inhibitors are continually required to deal with melanogenesis caused problems effectively with a few side effects. Therefore, the effects of various natural source extracts on human skin whitening and anti-melanogenesis have drawn significant attention, and numerous studies have been conducted to verify their benefits in cosmetic formulations [8,9].…”
Section: Introductionmentioning
confidence: 99%